2013
DOI: 10.1029/161gm23
|View full text |Cite
|
Sign up to set email alerts
|

West Florida Shelf Circulation on Synoptic, Seasonal, and Interannual Time Scales

Abstract: The continental shelf ocean circulation is driven by a combination of local and deep ocean forcing, where the local forcing is by surface momentum and buoyancy (heat and fresh water) fluxes and by land-derived fresh water fluxes, and the deep ocean forcing is by momentum and buoyancy fluxes transmitted across the shelf break. While all continental shelves share the same response physics, their geom etries, river distributions, and boundary currents make their individual behaviors unique. Here we consider the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…Our 6 yr mean wind and surface current fields (Fig. 16) reproduced many known features identified in earlier studies (e.g., Weisberg, 2002, 2003;Weisberg et al, 2005). Annual riverine nitrogen input (12.76 × 10 9 mol N yr −1 ) to the WFS was comparable to that to the BOC shelf (12.42 × 10 9 mol N yr −1 , Table 2).…”
Section: Wfssupporting
confidence: 72%
“…Our 6 yr mean wind and surface current fields (Fig. 16) reproduced many known features identified in earlier studies (e.g., Weisberg, 2002, 2003;Weisberg et al, 2005). Annual riverine nitrogen input (12.76 × 10 9 mol N yr −1 ) to the WFS was comparable to that to the BOC shelf (12.42 × 10 9 mol N yr −1 , Table 2).…”
Section: Wfssupporting
confidence: 72%
“…He and Weisberg (2002) found that such a current could be established in spring over the western part of the WFS. This potential shelf route for the southward advection of MR waters in the GoM is also mentioned in Weisberg et al (2005), but it has never been actually observed in the case of longdistance MR water export episode. Another novel aspect of our study is to employ a unique set of observations that confirms model-based findings.…”
Section: Introductionmentioning
confidence: 89%
“…The west Florida shelf (WFS) displays a strong coherent response to synoptic-scale alongshore wind forcing Weisberg 1999a, 1999b;Weisberg et al 2000Weisberg et al , 2005 that is also observed on the inner SWF shelf . According to , synoptic-scale upwelling (downwelling) alongshore winds, together with the coastal constraint, results in barotropic alongshore currents over the shelf aligned with the wind direction at the surface and balanced by set-up (set-down) of the coastal sea level.…”
Section: Southwest Florida Shelf Dynamicsmentioning
confidence: 99%